Modulation of taste responsiveness by the satiation hormone peptide YY. Issue 12 (16th September 2013) - La Sala, Michael S.; Hurtado, Maria D.; Brown, Alicia R.; Bohórquez, Diego V.; Liddle, Rodger A.; Herzog, Herbert; Zolotukhin, Sergei; Dotson, Cedrick D.
Abstract : It has been hypothesized that the peripheral taste system may be modulated in the context of an animal's metabolic state. One purported mechanism for this phenomenon is that circulating gastrointestinal peptides modulate the functioning of the peripheral gustatory system. Recent evidence suggests endocrine signaling in the oral cavity can influence food intake (FI) and satiety. We hypothesized that these hormones may be affecting FI by influencing taste perception. We used immunohistochemistry along with genetic knockout models and the specific reconstitution of peptide YY (PYY) in saliva using gene therapy protocols to identify a role for PYY signaling in taste. We show that PYY is expressed in subsets of taste cells in murine taste buds. We also show, using brief‐access testing with PYY knockouts, that PYY signaling modulates responsiveness to bitter‐tasting stimuli, as well as to lipid emulsions. We show that salivary PYY augmentation, via viral vector therapy, rescues behavioral responsiveness to a lipid emulsion but not to bitter stimuli and that this response is likely mediated via activation of Y2 receptors localized apically in taste cells. Our findings suggest distinct functions for PYY produced locally in taste cells vs. that circulating systemically.—La Sala, M. S., Hurtado, M. D., Brown, A. R., Bohórquez, D. V., Liddle, R. A., , Herzog, H., Zolotukhin, S., Dotson, C. D., Modulation of taste responsiveness by the satiation hormone peptide YY. FASEB J. 27, 5022–5033 (2013). www.fasebj.org